Toxicity screening of two prevalent metal organic frameworks for therapeutic use in human lung epithelial cells - Wagner A (Dove Medical Press, 2019)
Alixandra Wagner,1,* Qian Liu,1,* Olivia L Rose,1,* Anna Eden,1 Aishwarya Vijay,1 Yon Rojanasakul,2 Cerasela Zoica Dinu1 1Department of Chemical and Biomedical Engineering, Benjamin M. Statler College of Engineering and Mineral Resources, West Virginia University, Morgantown, WV 26506, USA; 2Department of Basic Pharmaceutical Sciences, West Virginia University, Morgantown WV 26506, USA*These authors contributed equally to this workCorrespondence: Cerasela Zoica DinuDepartment of Chemical and Biomedical Engineering, M. Statler College of Engineering and Mineral Resources, West Virginia University, Benjamin, PO Box 6102, Morgantown, WV 26506, USATel +1 304 293 9338Fax +1 304 293 4139Email cerasela-zoica.dinu@mail.wvu.eduIntroduction: The flexibility and tunability of metal organic frameworks (MOFs), crystalline porous materials composed of a network of metal ions coordinated by organic ligands, confer their variety of applications as drug delivery systems or as sensing and imaging agents. However, such properties also add to the difficulty in ensuring their safe implementation when interaction with biological systems is considered.Methods: In the current study, we used real-time sensorial strategies and cellular-based approaches to allow for fast and effective screening of two MOFs of prevalent use, namely, MIL-160 representative of a hydrophilic and ZIF-8 representative of a hydrophobic framework. The two MOFs were synthesized “in house” and exposed to human bronchial epithelial (BEAS-2B) cells, a pertinent toxicological screening model.Results: Analysis allowed evaluation and differentiation of particle-induced cellular effects as well identification of different degrees and routes of toxicity, all in a high-throughput manner. Our results show the importance of performing screening toxicity assessments before introducing MOFs to biomedical applications.Discussion: Our proposed screening assays could be extended to a wider variety of cell lines to allow for identification of any deleterious effects of MOFs, with the range of toxic mechanisms to be differentiated based on cell viability, morphology and cell–substrate interactions, respectively.Conclusion: Our analysis highlights the importance of considering the physicochemical properties of MOFs when recommending a MOF-based therapeutic option or MOFs implementation in biomedical applications.Keywords: metal organic frameworks, real-time assay, high-throughput assessment